Pengaruh Kepemimpinan Transformasional, Komitmen Afektif Dan Kepuasan Kerja Terhadap Kinerja Anggota Kepolisian Di Seluruh Polsek Kabupaten Pandeglang - Muchtad Khairil Anwar; Darsa Darsa; Ahmad Sugianto (E-Journal Studia Manajemen, 2022)
Research to explore problems and solve problems of job performance of police officers at the Pandegelang Police used a causal study of police officers at the Pandegelang Police, Banten, Indonesia, for a sample of 46 Apparatus. Data for each variable was collected separately by respondents who filled out a questionnaire. The method used in this research is quantitative survey method, while the analysis technique used is regression analysis. The results prove that there is a positive direct effect of transformational leadership on job performance. This means that an increase in transformational leadership will improve job  performance of the Pandeglang Police Apparatus. There is a direct positive effect of effective commitment on job performance. This means that an increase in effective commitment will improve job performance of the Pandeglang Police Apparatus. There is a positive direct effect of job satisfaction on job performance. This means that an increase in the job satisfaction of the police apartment will affect job performance improvement of the Pandeglang Police Apparatus. There is a positive direct influence between transformational leadership, effective commitment and job satisfaction on job performance. This means that increased transformational leadership, effective commitment and job satisfaction will affect job  performance improvement of the Pandeglang Police Apparatus. These findings recommend that organizations should consider transformational leadership, effective commitment and job satisfaction variables in human resource planning and development at the Pandegelang Police.